The Effect of Security, Service Quality, Operations and Information Management, Reliability &Trustworthiness on E-Loyalty moderated by Customer Satisfaction on the Online Shopping Website - Andala Rama Putra Barusman (International Journal of Supply Chain Management, 2019)
The aims of this study is to examine the effect of security, quality of service, operations and information management and trustworthiness on E-loyalty customer moderated by customer satisfaction for online shop website. The sample was taken using random sampling technique as many as 1300 respondents. The data was tabulated and processed using questionnaires, interviews, observation and documentation. The results of this study showed that security, information management, reliability and trustworthiness has positive and direct impact on customer satisfaction. Meanwhile, service quality has negative and indirect impact on customer satisfaction. This study also showed that customer satisfaction has positive and direct impact to E-loyalty customer for online shopping website.